Randomized open‐label phase II study comparing oxycodone–naloxone with oxycodone in early return of gastrointestinal function after laparoscopic colorectal surgery. Issue 1 (20th October 2016) - Creamer, F.; Balfour, A.; Nimmo, S.; Foo, I.; Norrie, J. D.; Williams, L. J.; Fearon, K. C.; Paterson, H. M.
Abstract: Background: Combined oral modified‐release oxycodone–naloxone may reduce opioid‐induced postoperative gut dysfunction. This study examined the feasibility of a randomized trial of oxycodone–naloxone within the context of enhanced recovery for laparoscopic colorectal resection. Methods: In a single‐centre open‐label phase II feasibility study, patients received analgesia based on either oxycodone–naloxone or oxycodone. Primary endpoints were recruitment, retention and protocol compliance. Secondary endpoints included a composite endpoint of gut function (tolerance of solid food, low nausea/vomiting score, passage of flatus or faeces). Results: Eighty‐two patients were screened and 62 randomized (76 per cent); the attrition rate was 19 per cent (12 of 62), leaving 50 patients who received the allocated intervention with 100 per cent follow‐up and retention (modified intention‐to‐treat cohort). Protocol compliance was more than 90 per cent. Return of gut function by day 3 was similar in the two groups: 13 (48 per cent) of 27 in the oxycodone–naloxone group and 15 (65 per cent) of 23 in the control group (95 per cent c.i. for difference −10·0 to 40·7 per cent; P = 0·264). However, patients in the oxycodone–naloxone group had a shorter time to first bowel movement (mean(s.d.) 87(38) h versus 111(37) h in the control group; 95 per cent c.i. for difference 2·3 to 45·4 h, P = 0·031) and reduced total (oral plus parenteral) opioid consumption (mean(s.d.) 78(36) versus 94(56) mg respectively; 95 per cent c.i. for difference −10·2 to 42·8 mg, P = 0·222). Conclusion: High participation, retention and protocol compliance confirmed feasibility. Potential benefits of oxycodone–naloxone in reducing time to bowel movement and total opioid consumption could be tested in a randomized trial. Registration number: NCT02109640 (https://www.clinicaltrials.gov/ ). Abstract : Subtle differences